2007
DOI: 10.1080/15715124.2007.9635318
|View full text |Cite
|
Sign up to set email alerts
|

Decision support systems for managing the water resources of the Komati River Basin

Abstract: The Komati River Basin is a trans-boundary watercourse shared by the Republic of South Africa (RSA), the Kingdom of Swaziland (KoS) and the Republic of Mozambique. The Komati Basin Water Authority (KOBWA) is charged with the management of the river basin under a treaty signed between RSA and Swaziland of which consent was given by Mozambique in a separate Agreement. KOBWA developed Decision Support Systems (DSS) to manage the system. These include DSS for: (i) long-term water allocation (yield model) between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…They concluded that the reduction of natural fresh water fluxes (small floods) has a negative impact on the state of the environment and hence on the goods and services the estuary yields. Dlamini (2007) describes Decision Support Systems (DSS) developed by Komati Water Basin Authority (KOBWA) to manage the Komati system. These include DSS for: (i) long-term water allocation (yield model) between the countries, (ii) short-term water allocation (rationing model), and (iii) day-to-day water release (hydraulics model).…”
Section: Other Water Resources Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…They concluded that the reduction of natural fresh water fluxes (small floods) has a negative impact on the state of the environment and hence on the goods and services the estuary yields. Dlamini (2007) describes Decision Support Systems (DSS) developed by Komati Water Basin Authority (KOBWA) to manage the Komati system. These include DSS for: (i) long-term water allocation (yield model) between the countries, (ii) short-term water allocation (rationing model), and (iii) day-to-day water release (hydraulics model).…”
Section: Other Water Resources Studiesmentioning
confidence: 99%
“…An extensive water-monitoring program has been put in place to improve the effectiveness of these DSSs. Dlamini (2007) reports that there has been a wide acceptance of the DSS by the users in the basin since they enable water users and water managers to make transparent water management decisions. Hellegers et al (2009) proposed a method that combines remote sensing and socioeconomic analyses to assess spatial variation in crop water productivity (CWP) and economic water productivity (EWP) in the Inkomati basin.…”
Section: Other Water Resources Studiesmentioning
confidence: 99%
See 1 more Smart Citation